2017
DOI: 10.1016/j.jue.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Transfer taxes and household mobility: Distortion on the housing or labor market?

Abstract: We estimate the effect of the UK Stamp Duty Land Tax (SDLT) -a transfer tax on the purchase price of property or land -on different types of household mobility using micro data. Exploiting a discontinuity in the tax schedule, we isolate the impact of the tax from other determinants of mobility. We compare homeowners with self-assessed house values on either sides of a cut-off value where the tax rate jumps from 1 to 3 percent. We find that a higher SDLT has a strong negative impact on housing-related and short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 25 publications
2
30
0
1
Order By: Relevance
“…Past OECD research has shown that excessively tight rent regulations can affect the supply of new dwellings and maintenance of the existing rental housing stock and hamper the development of the rental market (Caldera and Johansson, 2013 [27]). This in turn, can lead to shortages of housing supply, exacerbating speculative housing bubbles and increases in household debt posing significant vulnerabilities for macroeconomic stability and economic growth (Hermansen and Röhn, 2016 [28]).…”
mentioning
confidence: 99%
“…Past OECD research has shown that excessively tight rent regulations can affect the supply of new dwellings and maintenance of the existing rental housing stock and hamper the development of the rental market (Caldera and Johansson, 2013 [27]). This in turn, can lead to shortages of housing supply, exacerbating speculative housing bubbles and increases in household debt posing significant vulnerabilities for macroeconomic stability and economic growth (Hermansen and Röhn, 2016 [28]).…”
mentioning
confidence: 99%
“…This alternative nevertheless has a negative score with regard to its impact on property markets. Studies on the stamp duty have revealed that taxation at transactions may have a considerable negative effect on household mobility (Hilber and Lyytikäinen, 2017). The system may make it very unattractive to move away from properties with low ground rents in areas that have become attractive.…”
Section: Comparison Of Alternativesmentioning
confidence: 99%
“…In an ideal world, the existing council tax and the SDLT-two highly distortive taxes (Hilber, 2015a;Hilber and Lyytikäinen, 2015)-are replaced with a proper annual local property tax with automatic annual revaluation based on neighborhood-specific price changes. Such a tax reform could be designed to be revenue neutral in the aggregate.…”
Section: Foreign Exchangementioning
confidence: 99%
“…They lose out because they (1) live in artificially cramped housing and (2) are increasingly priced out from moving to a larger home that would be more adequate for their growing family. Trading up becomes increasingly difficult, and the problem is made worse by the UK Stamp Duty Land Tax (SDLT) that heavily taxes housing transactions (Hilber, 2015c;Hilber and Lyytikäinen, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation